Metabolic and Genetic Determinants of Lipid Metabolism Disruption in Non-Alcoholic Fatty Liver Disease - O. Yu. Kytikova; T. P. Novgorodtseva; Yu. K. Denisenko; D. A. Kovalevsky (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim. To present literature data on the metabolic and genetic mechanisms of impaired fatty acid (FA) synthesis in the development and progression of non-alcoholic fatty liver disease (NAFLD).General findings. NAFLD is a widespread disease progressing from steatosis to non-alcoholic steatohepatitis (NASH), increasing the risk of cirrhosis, liver failure and hepatocellular carcinoma. Progression of NAFLD and the development of NASH are closely related to lipid metabolism disorders caused not only by insufficient alimentary intake of fatty acids, but also by a decrease in the efficiency of their endogenous processing. The regulation of fatty acid metabolism involves enzymes desaturase (FADS1, FADS2) and elongase (ELOVL2 and ELOVL5) fatty acids. Desaturases are encoded by the FADS1 and FADS2 genes for fatty acid desaturases. Polymorphisms in the genes of fatty acid desaturases determine the effectiveness of PUFA endogenous processing. Violations in the activity of FADS1 and FADS2 and their genes are accompanied by dysregulation of the metabolic pathway involved in the biosynthesis of fatty acids. This leads to the damage of cell membranes, whose main components are represented by phospholipids. The progression of NAFLD is associated with the powerful toxicity of lipids released in the liver parenchyma upon the loss of the cell biomembrane integrity.Conclusions. Further research into the NAFLD genetic mechanisms regulating the metabolism of fatty acids appears to be promising for a deeper understanding of the pathogenesis of this multifactorial disease.